Secular, Islamic or Muslim Feminism? The Places of Religion in Women’s Perspectives on Equality in Islam - Zora Hesová (Gender a Výzkum, 2019)
he Western focus on ‘Islamic feminism’ takes two extreme forms: it is often dismissed as an oxymoron for attaching a religious (patriarchal) adjective to an emancipatory feminist project, or it is hailed as a road to a liberal, reformed Islam. Many Muslim feminists refuse to use this term; some reject feminism outright. There is consequently a tension within the term that many Muslim women activists acknowledge. In order to gain a better understanding of how religious and secular discourses combine in ‘feminism in Islam’, this text aims to examine the place of religion in women’s emancipatory strategies.